Cryopreservation of Musa germplasm - Panis, Bartholomeus (Bioversity International, 2009)
Bananas and plantains (Musa species) are important food staples in the tropics and subtropics. This germplasm needs to be safely conserved to ensure that it is available for future breeding efforts for improved production and adaptation to changing environmental conditions. This booklet provides information on cryopreservation methodologies suitable for Musa species.